Efficient Design of Flexible and Low Cost Paper-Based Inkjet-Printed Antenna - A. M. Mansour; N. Shehata; B. M. Hamza; M. R. M. Rizk (International Journal of Antennas and Propagation)
A new, efficient, flexible, and cheap antenna designed at 1.57 GHz microstrip patch antenna based on simple inkjet printer with improved performance using silver nanoparticles ink is developed. The antenna is printed on a kind of flexible substrate “glossy paper,” to offer the advantage of light and flexibility for different applications. The performance of silver nanoparticles ink has been studied through inkjet printing versus postsynthesis annealing and multilayer printing. The conductivity has been improved to have promising values up to 2 Ω/cm at temperatures up to 180°C. The surface morphology of the circuits has been analyzed using SEM with mean diameter of the nanoparticles around 100 nm, uniform surface distribution, and mean thickness of the printed layer around 230 microns. Also, a simple design of a coplanar waveguide (CPW) monopole Z-shaped antenna has been considered as an application of fabricated printed antenna using the studied silver nanoparticles ink through a cheap printer.